Domestic and Foreign Incomes and Trade Balance - A Case of South Asian Economies - Iqbal, Mubasher; Kalim, Rukshana; Arshed, Noman (Asian Development Policy Review, 2020)
The persistent trade deficit is one of the common issues of South Asia specifically, Bangladesh, India and Pakistan. While an increase in domestic income can help in the movement from import based economy to the economy with export capacity (quadratic effect), but quadratic effect of the world income must also be evaluated as it creates demand for exports. This study has adapted Kuznets curve hypothesis to propose U shaped and inverted U shaped relationship of domestic income and world income respectively on the trade balance. By estimating Panel ARDL model using the data for three selected economies, this study has confirmed the U shaped and inverted U shaped relationship with respect to domestic income and world income respectively. Further policymakers can moderate domestic income effect to minimize trade deficit by boosting terms of trade and FDI.